CEO turnover and corporate innovation: What can we learn from Chinese listed companies - Shujun Sun; Haiwei Jiang (Frontiers in Psychology, 2022)
Using data of China’s listed companies from 2000 to 2016, we employ a staggered difference-in-difference (DID) approach to identify the causal effects of CEO turnover on corporate innovation. First, we find that listed companies with CEO turnover experienced an average increase of 9.5% in the quantity of innovation and 8.9% in innovation quality after the change. The dynamic effect test supports the parallel trend condition, and the placebo test rules out the nonrandom selection issue. Second, the heterogeneity tests show that CEO turnover plays a more prominent role in promoting innovation for listed firms with CEO duality, high financial constraints, and in high-tech industries. Third, CEO turnover affects corporate innovation by driving top management team reorganization and promoting R&D input. This paper has important implications for the understanding of the role of CEO turnover in companies’ innovation, as well as for strategy formulation and implementation.